Endoscopic Ultrasound Guided Fine Needle Aspiration for Diagnosis of Pancreatic Tuberculosis - Sharma, Vishal; Rana, Surinder S; Bhasin, Deepak K (JOP. Journal of the Pancreas, 2013)
No abstract available. Image: Nehru Hospital. Chandigarh, India.